2022
DOI: 10.3389/fphar.2022.880090
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Bevacizumab Biosimilars Compared With Reference Biologics in Advanced Non-small Cell Lung Cancer or Metastatic Colorectal Cancer Patients: A Network Meta-Analysis

Abstract: Background: Bevacizumab biosimilars are slowly making their way into cancer treatment, but the data on their efficacy and safety in cancer patients are still poor. We systematically summarized the current evidence for the efficacy and safety of bevacizumab biosimilars in patients with advanced non-small cell lung cancer (NSCLC) or metastatic colorectal cancer (CRC).Methods: This review searched CNKI, VIP, PubMed, Medline (Ovid), Embase, and Cochrane Library (Ovid) for randomized controlled trials of bevacizuma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
(87 reference statements)
0
11
0
Order By: Relevance
“…It was revealed that efficacy and safety profiles of bevacizumab biosimilars closely resembled those of the reference biologics for NSCLC and CRC patients with metastatic disease. Intriguingly, the various varieties of bevacizumab biosimilars exhibited negligible differences in terms of their therapeutic efficacy and safety 12 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It was revealed that efficacy and safety profiles of bevacizumab biosimilars closely resembled those of the reference biologics for NSCLC and CRC patients with metastatic disease. Intriguingly, the various varieties of bevacizumab biosimilars exhibited negligible differences in terms of their therapeutic efficacy and safety 12 …”
Section: Discussionmentioning
confidence: 99%
“…The focus is on understanding how this biosimilar impacts wound healing, considering that Bevacizumab's mechanism of inhibiting vascular endothelial growth factor (VEGF) could potentially impede this process. This evaluation is crucial to determine if the biosimilar offers similar or improved outcomes compared with the original Bevacizumab, including its effects on wound healing rates and adverse effects, as well as its cost‐effectiveness in clinical practice 8–12 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 73 The Bayesian network approach helps address this issue by producing novel outputs such as treatment rankings, odds ratios, and probability distributions. 74 Several such studies have been performed in lung cancer, including evaluating safety and efficacy of bevacizumab biosimilars, 75 determining optimal platinum-based chemotherapy for early-stage resected NSCLC, 76 how smoking status influences effect of targeted therapy, 77 and choice of first-line treatment for patients on the basis of PD-L1 expression. 78 , 79 , 80 …”
Section: Treatmentmentioning
confidence: 99%